Mobile Forensic Investigation on iOS & Android Smartphones: Case Study Investigation on WhatsApp - Zakarneh, Shadi Khaled (Universitas Sanata Dharma, 2024)
Following the exponential growth of information and communication technologies, the smartphone market, as well as advances in wireless data networks (3G and 4G), has accelerated. Mobile apps for social networking and instant messaging have been created by these firms. Other instant messaging (IM) smartphone programs like WhatsApp (WA), Viber, and IMO have also been created. WA is the most widely used instant messaging program. With WA, you can send and receive messages in a variety of formats, including text, voice, video, and documents. Various cybercrime incidents were committed through WA's. WA use leaves several artifacts that may be examined to detect the digital evidence. In addition, iOS and Android are two of the most popular smartphone operating systems. Because of this, the inquiry will involve the use of forensic investigative techniques and methodologies. Forensics on both iOS and Android cellphones were utilized to investigate a digital crime that was believed to have been perpetrated in WA. To conclude the investigation, we analyzed chat logs, phone records, and other media to gather proof. Legal framework and established processes were used to guarantee that evidence was preserved from change or destruction and that the witness's account was acceptable in court throughout the investigative process. It was finally stated that the inquiry and evidence had been presented. As a result, WA forensic artifacts might be evaluated and found effectively utilizing the mobile forensic procedure.